Articulating English to specific content areas at Pontificia Bolivariana University - Monsalve T, María Isabel; Montoya E, Patricia; Posada R, Claudia; Serna D, Héctor Manuel (Colombian Applied Linguistics Journal, 2005)
The Pontifi cia Bolivariana University has decided to look for alternatives to make the study of English more relevant for studentsʼ professional practice. The authors of this article consider that Content Based Instruction (CBI) offers scenarios in which content and language learning can be developed in order to fulfi ll this goal. This article provides information in regards to the fi rst stage of a fi ve-phased project, designed for the Pontifi cia Bolivariana University. The fi rst phase, which is described in this article, presents the context and background of the project, the CBI theoretical background intended to structure the CBI - Universidad Pontifi cia Bolivariana (UPB) model, the methodology developed to articulate content and language for this experience, the line of inquiry and some project implications.